Does ESG Score Impact on Financial Performance? The Moderating Role of Female Board of Directors - Permatasari Cahyaningdyah; Ulfa Rahmawati; Oktavia Nur Orbentega (Universitas Teknologi Yogyakarta, 2025)
This study investigates the influence of Environmental, Social, and Governance (ESG) on corporate financial performance (FP), and the role of female board of directors among ESG and corporate financial performance. Sustainability issues have been on the rise in recent decades, leading to increased market interest in transparency of companies' economic, environmental, and social performance (ESG). Companies carry out ESG performance as a form of responsibility to stakeholders. Disclosure of ESG performance that is responded positively by investors can impact the company's financial performance. With a quantitative method, the samples of this study are companies listed in the ESG Leader Index on the IDX in 2021-2023. The data collection technique uses purposive sampling. The number of samples is 60 companies. Hypothesis is tested with regression analysis. The empirical findings show that ESG, as measured by ESG risk, has a negative impact on corporate financial performance. In addition, female board of directors strengthen association of ESG and corporate financial performance. This study contributes to enriching the literature on stakeholder theory in the scope of corporate awareness of ESG. This research makes a practical contribution that companies that have good environmental and social responsibility do not necessarily have optimal financial performance. Hence investors and shareholders also need to understand this matter before making their investments.